Editorial Tribute to Al-Marhum Associate Professor Dr. Wan Suhaimi bin Wan Abdullah - Saari, Che Zarrina (Afkar: Jurnal Akidah dan Pemikiran Islam, 2024)
It is with a deep sense of loss and profound respect that we dedicate this issue of AFKAR vol. 26 issue 1 (2024), 24 years after its inception, to the memory of its founder, our esteemed pioneer and first manager, Al-Marhum Associate Professor Dr. Wan Suhaimi bin Wan Abdullah, who passed away on February 27th, 2024 [17 Sha‘ban 1445H].